Håbets mellemrum - Nutid og fremtid i Grundtvigs tolkning af håbsbegrebet - Højlund, Christian (Grundtvig-Studier, 1977)
The Interval of Hope: Present and Future - Grundtvig’s Interpretation of the Concept of Hope by Christian Højlund In his earlier sermons (1810-15) Grundtvig interpreted the Christian hope in the orthodox Lutheran way: hope was bound to the words of the Bible and not until these were finally fulfilled and the last days entered upon would the hope of Christ’s kingdom and eternal life also be fulfilled. Until then, the pilgrim on earth must be satisfied with allowing himself to be guided by the star of hope before him. In other words, hope was a purely future concept. This was also the case with the rationalists. But with them, the fulfilment was further conditional upon man’s own reason and virtue. When Grundtvig took over a living in Copenhagen during Advent 1822 he began to do serious battle with this theology. By letting reason be the only accepted way to the hope in the Bible the rationalists had gained a monopoly on the right way to interpret the scriptures. They had taken hope from the Church and made it a false hope dependent on man’s own efforts. His attack on the rationalists partly dealt a blow to Grundtvig’s own view of the scriptures. The authenticity of hope could no longer rest on one or other interpretation of the scriptures. Only the living gospel, which had sounded from generation to generation in the Church, witnessed the truth of hope. Without a living gospel there is no hope. The Holy Spirit was the Church’s own interpreter of the scriptures and the living word preached in the church was the right basis for hope. The way to the loud and clear words from the Lord’s own mouth through baptism and communion was now open for Grundtvig. Now hope was revealed as the hope of Christ and changed its course towards God’s kingdom inasmuch as the Jesus child was reborn in the rebirth of baptism and prayed alongside the child when it faltered over the Lord’s prayer. There the hope of the eschatological meal, which is anticipted in Holy Communion, will be fulfilled and the glorified Christ will be one with the baptised. The birth of hope, its growth and fulfilment thus for Grundtvig became bound up with the order of service from baptism to communion. He thereby achieved two things, I) Hope acquired a new dimension. From being solely a comforter for the future it brought the impact of God’s kingdom into the present as well, with peace and justice and joy experienced in the loud and clear address of the church service, II) He avoided a mere visionary proclamation of hope, which would force God’s kingdom forward and make itself master over it. Hope was Christ Himself, both in its origin and in its fulfilment. But when in the 1830’s Grundtvig unreservedly emphasized the created human life as the prerequisite and the linking-point for God’s saving address, hope became really ridiculous and indefensible in the eyes of the world. This was precisely the case with Jesus* birth as a human baby. And this was how it must therefore be with the rebirth of baptism. There and only there could God’s Kingdom begin to grow. Thus the Christian Church, in Grundtvig’s opinion, had to give up its role as guardian, forcing people to believe. It had to stick to the naked word of the gospel. Yet at the same time it was Grundtvig’s conviction that wherever this word met together in free interplay with created man in his local, human context, the true hope could and would be born, and God’s Kingdom could grow on earth - invisible but real.